Auditory function following post‐dural puncture headache treated with epidural blood patch. A long‐term follow‐up. Issue 10 (24th June 2015) - Darvish, B.; Dahlgren, G.; Irestedt, L.; Magnuson, A.; Möller, C.; Gupta, A.
<x xml:space="preserve">Abstract</x> Background Epidural analgesia is commonly used for pain management during labor. Sometimes, accidental dural puncture (ADP) occurs causing severely debilitating headache, which may be associated with transient hearing loss. We investigated if auditory function may be impaired several years after ADP treated with epidural blood patch (EBP). Methods Sixty women (ADP group) without documented hearing disability, who received EBP following ADP during labor between the years 2005–2011 were investigated in 2013 for auditory function using the following tests: otoscopic examination, tympanometry, pure tone audiometry, and transient‐evoked otoacoustic emissions. Additionally, they responded to a questionnaire, the Speech, Spatial and Qualities (SSQ) of hearing, concerning perceived hearing impairment. The results were compared to a control group of 20 healthy, non‐pregnant women in the same age group. Results The audiometric test battery was performed 5.2 (1.9) years after delivery. No significant differences were found between the ADP and the control groups in tympanometry or otoacoustic emissions. Pure tone audiometry revealed a significant but small (< 5 dB) difference between the ADP and control groups (P < 0.05). The ability to hear speech in noise as measured by SSQ was significantly reduced in the ADP group compared to the control group (P < 0.05). Conclusions A minor hearing loss was detected in the ADP group compared to the control group in pure tone audiometry in some women and during speech‐in‐noise component several years after accidental dural puncture treated with an epidural blood patch. This small residual hearing loss has minor clinical significance.